EFEKTIVITAS VIDEO ANIMASI DALAM KOMUNIKASI PUBLIK KEPOLISIAN UNTUK MENANGGULANGI PERILAKU PATOLOGI REMAJA DI KABUPATEN SIDENRENG RAPPANG - Ahmad Naufal; Jamaluddin Ahmad; Andi Nilwana; Ahmad Mustanir (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
The objective of this study is to analyze the effectiveness of animated video media as a public communication tool in community guidance programs conducted by the Sidenreng Rappang Police to address adolescent pathological behavior. The method used was descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation studies involving adolescents, parents, teachers, community leaders, and police officers. The findings reveal that animated videos are highly effective in: (1) attracting attention and enhancing adolescents' understanding of the dangers of pathological behaviors such as drug abuse and brawls, due to their visual, narrative, and relevant format; (2) opening spaces for interactive dialogue among police, schools, and families, which strengthens message internalization; and (3) contributing to a tangible decrease in student brawl cases. This success is driven by a humanist and educative communication approach, contrasting with previous repressive methods. In conclusion, animated video media is proven to be an effective and innovative public communication tool for the police in preventing adolescent pathological behavior, with the note that it needs to be combined with face-to-face approaches to reach all community segments.